NIAID Workshop Report: Systematic Approaches for ESKAPE Bacteria Antigen Discovery - Inka Sastalla; Keehwan Kwon; Clayton Huntley; Kimberly Taylor; Liliana Brown; Tamika Samuel; Lanling Zou (Vaccines)
On 14–15 November 2023, the National Institute of Allergy and Infectious Diseases (NIAID) organized a workshop entitled “Systematic Approaches for ESKAPE Bacteria Antigen Discovery”. The goal of the workshop was to engage scientists from diverse relevant backgrounds to explore novel technologies that can be harnessed to identify and address current roadblocks impeding advances in antigen and vaccine discoveries for the ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species). The workshop consisted of four sessions that addressed ESKAPE infections, antigen discovery and vaccine efforts, and new technologies including systems immunology and vaccinology approaches. Each session was followed by a panel discussion. In total, there were over 260 in-person and virtual attendees, with high levels of engagement. This report provides a summary of the event and highlights challenges and opportunities in the field of ESKAPE vaccine discovery.